(3QSGdI NeGQ Hf NjT GdSdjeGfj GdYcGhjs - (3NeGQ Hf LjT GdSdeGfj GdYcGhjs ((3MeRg Hf Ydj Hf CMeO s)
(3ChdgG (B:s
(3JhcdJ Ydi CejQ GdeDefjf Ld PcQg hHg CSJYjf aj cd GdCehQ s
(3BNQgG (B:s
(3hPdc Hbhg ehdGfG Ld PcQg dGTQjc dg hgh MSHj hfYe GdfUQ GdoeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B27s
(3QSGdI ef QSGFd GdOQhRs
(3fSNI KGdKIs
(3eUOQ GbJfGA GdCUd (B:s
(3GdLGeYI GdCeQjcjI aj HjQhJ s
Keywords: (3GdJhMjO hGdedd hGdfMds